Mitochondrial Diseases: A Diagnostic Revolution. Issue 9 (September 2020) - Schon, Katherine R.; Ratnaike, Thiloka; van den Ameele, Jelle; Horvath, Rita; Chinnery, Patrick F.
Abstract : Mitochondrial disorders have emerged as a common cause of inherited disease, but are traditionally viewed as being difficult to diagnose clinically, and even more difficult to comprehensively characterize at the molecular level. However, new sequencing approaches, particularly whole-genome sequencing (WGS), have dramatically changed the landscape. The combined analysis of nuclear and mitochondrial DNA (mtDNA) allows rapid diagnosis for the vast majority of patients, but new challenges have emerged. We review recent discoveries that will benefit patients and families, and highlight emerging questions that remain to be resolved. Highlights: Reaching a molecular diagnosis in a patient with mitochondrial disease can be a complex process, both clinically and genetically. The diagnostic process for mitochondrial disease is undergoing a dramatic transition, moving away from a histological and biochemical approach to a primarily genetic approach. Whole-genome sequencing (WGS) can provide a genetic diagnosis for most patients. This has the added advantage of being able to diagnose mitochondrial disease in patients not thought to have the disorder, and to diagnose other non-mitochondrial diseases that resemble mitochondrial disorders. When WGS is negative, complementary phenotyping and sequencing approaches provide an additional strategy to increase the diagnostic yield. A collaborative community of clinicians and researchers allows extensive data-sharing across the globe, accelerating gene discovery and improving our understanding of how mutations cause disease.